"Bàn về hợp tác xã" hay sự phát triển và vận dụng sáng tạo logic biện chứng của Lenin - Đặng, Hà Chi (Tạp chí giáo dục, 2023)
After the October Revolution, the seeds of socialism in the society of the Soviet began to emerge and develop, although still a very primitive occurrence. Lenin had to advance and creatively implement dialectical logic to have the ability to detect and realize those primitive "cells." It had fulfilled by Lenin based on two main points: to rehearse the essential abstraction distributed as the starting point corresponding to the possibilities of the future society that is still in its infancy; to discover the cooperative system as the basis, the starting point, the commencement of theory and practice to achieve the immediate aim of moving toward socialism, and finally toward communism. In this article, the authors clarify those theoretical and practical contributions of Lenin, thereby contributing to the further development of dialectical logic in general and the conceiving of socialism in particular.